WeiTsing: a new face of Ca2+-permeable channels in plant immunity - Feng-Zhu Wang; Jian-Feng Li (Stress Biology, 2023)
Abstract Plants employ pattern- and effector-triggered immunity (PTI and ETI) to synergistically defend invading pathogens and insect herbivores. Both PTI and ETI can induce cytosolic Ca2+ spikes, despite in different spatiotemporal patterns, to activate downstream Ca2+-dependent immune signaling cascades. While multiple families of Ca2+-permeable channels at the plasma membrane have been uncovered, the counterparts responsible for Ca2+ release from intracellular stores remain poorly understood. In a groundbreaking paper published recently by Cell, the authors reported that WeiTsing, an Arabidopsis endoplasmic reticulum (ER)-resident protein that was specifically expressed in the pericycle upon Plasmodiophora brassicae (Pb) infection, could form resistosome-like Ca2+-conducting channel and protect the stele of Brassica crops from Pb colonization. As the channel activity of WeiTsing was indispensable for its immune function, the findings highlight a previously underappreciated role of Ca2+ release from intracellular repertoire in promoting plant disease resistance.